Premenstrual Dysphoric Disorder Without Comorbid Psychiatric Conditions: A Systematic Review of Therapeutic Options. Issue 5 (September 2016) - Sepede, Gianna; Sarchione, Fabiola; Matarazzo, Ilaria; Di Giannantonio, Massimo; Salerno, Rosa Maria
Abstract : Objectives: Premenstrual dysphoric disorder (PMDD) is a disabling condition affecting approximately 2% to 8% of women during reproductive age. It has been recently included in the mood disorder section of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, but its treatment as a primary psychiatric illness is still debated, because of the high prevalence of other mental disturbances in PMDD patients. On the other hand, clear clinical guidelines for PMDD patients not suffering from comorbid mental conditions are not yet available. The aim of the present study was therefore to systematically review the original articles pertaining to the treatment of PMDD in adult women free of any current or previous psychiatric comorbidity. Methods: We searched PubMed to identify published studies on PMDD, including randomized controlled trials, open-label trials, and case series or case reports involving adult women with no history of comorbid mental conditions. The search was conducted in April 2015. Results: We found 55 studies fulfilling our inclusion criteria, 49 of them focused on pharmacological/chemical agents and the remaining 6 on nonpharmacological interventions. Conclusions: Based on the results of our qualitative synthesis, the best therapeutic option in the treatment of adult PMDD patients free of other mental disorders are selective serotonin reuptake inhibitor antidepressants (especially paroxetine and fluoxetine) and low doses of oral estroprogestins. Other interventions, such as light therapy, cognitive behavioral therapy, food supplements, and herbal medicines, showed promising effects, but other investigations are needed to confirm their efficacy.